O professor inserido em instituições de atendimento sócioeducativo a adolescentes em conflito com a lei: a mobilização dos saberes docentes - Finoqueto, Leila Cristiane Pinto (2007)
This research had as purpose to characterize the pedagogical knowledge fund manifested or declared by teachers from Socio-Educative Center of Assessment of Santa Maria/RS about their teaching practices and to contribute in parameters establishment for a set of actions in order to form teachers to act in specific institutions which assess adolescents in conflict to the law. In this way, we began to discuss the thematic Teacher Knowledge , considering that researches about teaching, about knowledge and about teacher practice, important aspects to make teaching professional. To make teaching professional, in its turn, necessitates of recognizing specific knowledge to teacher profession. In this way, this paper focuses on pedagogical practices of teachers from Elementary School Humberto de Campos, school inserted in one of the internment units from FASE/RS Fundação de Atendimento Sócio-Educativo de Rio Grande do Sul the CASE/SM Centro de Atendimento Sócio-Educativo de Santa Maria/RS. From the diversities of approaches and seeking the coherence with the characteristics of this research, we developed a qualitative inquiry called case study. For that, we observed classrooms, registered in a field diary, and we used questionnaires and interviews with the teachers form that school. There were also pieces of information from two ex-majors of the school. We used as information source Political-Pedagogic Project from this school, the PEMSEIS Programa de Execução de Medidas Sócio-Educativas e de Semiliberdade , Statute for the Child and Adolescent and Educational Laws and Directives. The pieces of information, obtained by these instruments and sources, after organized, answered the research questions in the following way: teachers present a professional career in which there is few preparation to act in this kind of institution; they are professionals that, influenced by characteristics of this context, they created some strategies/tricks that got possible the development of their activities or made they continued at school; their conceptions about the offender adolescent, about ressocialization and about the teaching context in which they have been acted are in conflict in the way that the real conditions show themselves incompatible to the teachers possibilities of action. The teachers, recognizing this institution limits, they did not show themselves able to construct possibilities of changes, because the solutions adopted had occurred in an isolated and sporadic way and due to individual initiatives.